Helicobacter pylori causes Hyperproliferation of the gastric Epithelium: Pre- and Post-Eradication indices of proliferating cell nuclear antigen - Brenes Pino, Fernando (1993)
Artículo científico -- Universidad de Costa Rica, Instituto de Investigaciones en Salud. 1993